Investigating the Pharmacognostic Potential of Indian Terminalia Spp. in the Treatment and Prevention of Yersiniosis - Wright, Mitchell Henry; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Yersinia enterocolitica is a major cause of food poisoning through contaminated meat products, causing the acute gastrointestinal disease yersiniosis. Many Terminalia spp. have documented therapeutic properties as general antiseptics, inhibiting the growth of a wide variety of bacterial species. Despite this, Indian Terminalia spp. extracts have not been tested for the ability to inhibit the growth of Y. enterocolitica. Methods: T. arjuna, T. catappa and T. chebula extracts were extracted by maceration and the extracts were investigated by disc diffusion assay for growth inhibitory activity against a clinical strain of Y. enterocolitica. The MIC values of the extracts were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: T. chebula fruit extracts displayed potent growth inhibitory activity in the disc diffusion assay against Y. enterocolitica. The methanolic and ethyl acetate T. chebula fruit extracts were particularly potent growth inhibitors, with MIC values of 85 and 64 µg/mL respectively. The aqueous fruit extract also displayed good growth inhibitory activity against Y. entero- colitica, albeit with a higher MIC value (653 µg/mL). The T. arjuna branch extract was moderately active (3000 µg/mL). All other extracts were either low efficacy, or completely devoid of growth inhibitory activity. All Indian Terminalia spp. extracts were nontoxic (LC50 values <1000 µg/mL) in the Artemia franciscana bioassay. Conclusions: The lack of toxicity and the potent growth inhibitory bioactivity of the T. chebula extracts against Y. enterocolitica indicates their potential as medicinal agents in the treatment and prevention of yersiniosis.
Keywords: Terminalia arjuna; Terminalia catappa; Terminalia chebula; Yersinia enterocolitica; Enterobacteriaceae; antibacterial activity; food poisoning; Ayurveda.